2015
DOI: 10.1371/journal.pone.0125627
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IL-6 Signaling Pathway by Curcumin in Uterine Decidual Cells

Abstract: IL-6 is a multifunctional pro-inflammatory cytokine and has been implicated in many gestational disorders including preterm birth. Currently, there are no appropriate therapeutic interventions available to circumvent inflammatory-mediated gestational disorders. Therefore, the goal of this study was to identify a safe and effective pharmacological compound to counterbalance inflammatory responses in the uterus. Curcumin, a naturally-occuring polyphenolic compound, has been widely used in alternative medicine to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 60 publications
(71 reference statements)
1
44
0
1
Order By: Relevance
“…Lipopolysaccharide significantly up-regulated the IL-1β transcripts, which is in accordance with the reports in the bovine epi- Similarly, topical application of curcumin along with substance P hastened the healing of cutaneous wounds by decreasing the mRNA levels for IL-1β and TNF-α (Kant et al, 2017). Curcumin completely abrogated the IL-1β-induced IL-6 expression in the human endometrial decidual cells, when used at a concentration of 5-30 µM without causing cell toxicity (Devi, DeVine, DeKuiper, Ferguson, & Fazleabas, 2015). Similarly, curcumin suppressed the TNF-α-induced F I G U R E 2 Effect of curcumin on lipopolysaccharide (LPS) and/or flagellininduced expression of (a) IL-1β (b) IL-6 (c) IL-8 and (d) TNF-α cytokines in the bubaline endometrial stromal cells.…”
Section: Re Sultssupporting
confidence: 88%
See 1 more Smart Citation
“…Lipopolysaccharide significantly up-regulated the IL-1β transcripts, which is in accordance with the reports in the bovine epi- Similarly, topical application of curcumin along with substance P hastened the healing of cutaneous wounds by decreasing the mRNA levels for IL-1β and TNF-α (Kant et al, 2017). Curcumin completely abrogated the IL-1β-induced IL-6 expression in the human endometrial decidual cells, when used at a concentration of 5-30 µM without causing cell toxicity (Devi, DeVine, DeKuiper, Ferguson, & Fazleabas, 2015). Similarly, curcumin suppressed the TNF-α-induced F I G U R E 2 Effect of curcumin on lipopolysaccharide (LPS) and/or flagellininduced expression of (a) IL-1β (b) IL-6 (c) IL-8 and (d) TNF-α cytokines in the bubaline endometrial stromal cells.…”
Section: Re Sultssupporting
confidence: 88%
“…Similarly, topical application of curcumin along with substance P hastened the healing of cutaneous wounds by decreasing the mRNA levels for IL‐1β and TNF‐α (Kant et al, ). Curcumin completely abrogated the IL‐1β‐induced IL‐6 expression in the human endometrial decidual cells, when used at a concentration of 5–30 µM without causing cell toxicity (Devi, DeVine, DeKuiper, Ferguson, & Fazleabas, ). Similarly, curcumin suppressed the TNF ‐ α‐induced production of IL‐1β, IL‐6 and IL‐8 expression of cell adhesion molecules in the human endometriotic stromal cells (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These drugs are primarily inhibitors of inflammatory pathway. Their targets included inhibition of NF-κB [5558], enhancers of antiinflammatory peroxisome proliferator activated receptor (PPARs) [59], and antioxidant N-acetyl cysteine[60,61], cytokine suppressive anti-inflammatory drugs [62,63], agents to regulate Glycogen synthase kinase 3 (GSK3), an enzyme crucial for inflammation homeostasis [64], surfactant protein-A and PGJ2 to down regulate TLR mediated inflammation [65,66], targeted IL-6[67], and IL-1β signaling [68] to reduce inflammation, over antiinflammatory suppression using IL-10[6971]. Although many of these (drugs) agents were successful in reducing inflammation or oxidative stress in vitro, some of them were shown to have toxic side effects in animal model trials or in clinical trials, and successful clinical trial outcomes are thus yet to be reported using any of these agents in reducing the risk of PTB.…”
Section: Introductionmentioning
confidence: 99%
“…81,82 In vivo and in vitro studies of CSC have shown that curcumin can inhibit the release and function of IL-6 in these cells. 83 Curcumin has also been found to be a potent inhibitor of IL-8 production, which reduces IL-8 receptor internalization, prevents acid-induced IL-8 production, and reduces IL-8 levels, in vitro. 83 Curcumin has also been found to be a potent inhibitor of IL-8 production, which reduces IL-8 receptor internalization, prevents acid-induced IL-8 production, and reduces IL-8 levels, in vitro.…”
Section: Effects Of Curcumin On Cscsmentioning
confidence: 99%